Higher Secondary Level Students’ Attitude toward Use of E-Learning Materials in Health and Population Education - Bishnu, CC (Journal of Health Promotion, 2018)
The study aimed to find out the “student’s attitudes towards the use of e-learning materials in health and population education” at higher secondary level. The study adopted descriptive and quantitative survey design. In order to collect information, a set of attitude scale was used for 200 students of higher secondary level in the Kathmandu valley. The collected data were organized, tabulated, analyzed and interpreted by using the simple statistical tools such as percentage and 2 –test at 0.05 level of significance. The result of the study showed that the school students have sufficient e-learning tools with suitable existing situation for teaching and learning health and population education. The students have positive attitude towards the use of e-learning materials in health and population education. Most of the students agreed that the e-learning tools are very useful for higher achievement as well as higher study, as they provide basic concept with motivation. Journal of Health Promotion Vol.6 2008, p.11-17